Pengaruh Model Pembelajaran Project Based Learning Berbasis Media Educaplay Terhadap Motivasi Belajar Fisika Siswa Pada Materi Hukum Newton Kelas X Mia Ma Muallimin Univa Medan - Emi Trisdayanti; Rofiqoh Hasan Harahap; Shinta Marito Siregar; Lia Afriyanti Nasution (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
This study investigates the effect of the Project Based Learning (PjBL) model integrated with Educaplay media on students’ motivation in learning Newton’s Laws. A quasi-experimental quantitative design was employed, involving an experimental class and a control class. Data were collected through achievement tests and motivation questionnaires, and analyzed using descriptive and inferential statistics. The findings show a substantial increase in students’ motivation in the experimental class, reaching 81.5%, compared to 68.7% in the control class. The hypothesis test yielded a significance value of 0.001 < 0.05, indicating a significant positive effect of the PjBL–Educaplay integration. Unlike previous studies focusing on general digital media effectiveness, this study highlights the specific advantage of combining PjBL with interactive platforms to enhance motivation in physics learning